2015
DOI: 10.1186/s12889-015-2021-x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the benchmark dose of urinary cadmium as the reference level for renal dysfunction: a large sample study in five cadmium polluted areas in China

Abstract: BackgroundItai-itai disease primarily results from cadmium (Cd) exposure and is known as one of the four major pollution diseases in Japan. Cd pollution is more serious in several areas of China than in Japan. However, there is still a lack of information regarding the threshold level of Cd exposure for the adverse health effects in the general Chinese population. This study aims to evaluate the reference value of urinary Cd (UCd) for renal dysfunction in a Chinese population as the benchmark dose lower confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 29 publications
(73 reference statements)
0
22
1
Order By: Relevance
“…However, only few studies, conducted in cadmium‐polluted Jinzu and Kakehashi river basin in Japan, have shown the allowable values of cumulative cadmium intake for cadmium‐induced health effects (Kobayashi et al, ; Kobayashi, Suwazono, Dochi, Honda, & Kido, ; Nogawa et al, ). Several studies in China have shown the reference level of UCd or BCd for cadmium‐induced renal dysfunction (Jin et al, ; Ke et al, ; Wang et al, ) or osteoporosis (Chen, Gan, Zhu, & Jin, ). However, no study has shown the reference level of dietary cadmium intake in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…However, only few studies, conducted in cadmium‐polluted Jinzu and Kakehashi river basin in Japan, have shown the allowable values of cumulative cadmium intake for cadmium‐induced health effects (Kobayashi et al, ; Kobayashi, Suwazono, Dochi, Honda, & Kido, ; Nogawa et al, ). Several studies in China have shown the reference level of UCd or BCd for cadmium‐induced renal dysfunction (Jin et al, ; Ke et al, ; Wang et al, ) or osteoporosis (Chen, Gan, Zhu, & Jin, ). However, no study has shown the reference level of dietary cadmium intake in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…This value is higher than that in studies involving other areas of China. One large sample study conducted in five Cd‐polluted provinces in China found that the BMD 10 /BMDL 10 of U‐Cd for women in the different areas varied from 1.16/1.00 to 3.20/1.94 μg/g Cr (1.87/1.69 μg/g Cr, if the data in the five provinces were combined) for β 2 ‐MG and from 3.14/2.18 to 6.10/4.05 μg/g Cr for NAG (95% cut‐off value) (Ke, Cheng, Zhang, et al, ; Ke, Ke, Jia, et al, ). Another study conducted in two Cd‐polluted areas in south and central China showed that the BMD/BMDL values of U‐Cd for 35‐55‐year‐old women were 1.07/0.44 and 2.12/0.53 μg/g Cr based on β 2 ‐MG and NAG, respectively, at a 90% cut‐off value and 5% BMR (Qi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Model selection was performed using Akaike's information criterion, in which the model with the lowest Akaike's information criterion value was preferred. The subjects were divided into five subgroups (i.e., U‐Cd: 0‐2, 2‐4, 4‐6, 6‐8 and >8 μg/g Cr; B‐Cd: 0‐1, 1‐2, 2‐4, 4‐6 and >6 μg/L), which were selected based on previous studies (Ke, Cheng, Li, et al, ; Ke, Cheng, Zhang, et al, ) and the range and distribution of Cd exposure in the present study. BMD/BMDLs corresponding to an additional risk (BMR) of 5% and 10% were calculated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, safe levels of U-Cd have been determined differently in different studies, because even the 0.5 μg Cd/g creatinine level commonly found in the non-smoking population and in people living in areas without cadmium contamination has been found to have adverse effects on health ( 3 , 4 ). However, the WHO has established that U-Cd levels not exceeding 2 μg/g creatinine are safe for the general population ( 5 , 6 ). Thus, the safety margin between the cadmium level found in the general population and that causing cadmium toxicity is unclear.…”
Section: Introductionmentioning
confidence: 99%